(untitled) (Conferencea, 2023)
This article explores the topic of learning strategies in the context of blended learning. Blended learning combines traditional teaching methods with online components, offering students flexibility and personalized learning experiences. The article examines three key strategies: active learning, self-regulated learning, and collaborative learning. Active learning stimulates student engagement, develops critical thinking skills, and enhances motivation. Self-regulated learning fosters autonomy and lifelong learning skills, while collaborative learning promotes social interaction and communication skills. Implementing these strategies in blended learning enhances learning effectiveness, improves motivation, and cultivates key skills necessary for successful adaptation to the modern educational environment.